"Working Lives": The use of auto/biography in the development of a sociological imagination - Stephenson, Carol; Stirling, John; Wray, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2015)
This article critically evaluates the attempt of the authors to develop a sociological imagination within first-year undergraduate students studying the discipline of sociology at a British university. Through a sociological analysis of biography and autobiography (of both teachers and students), we attempted to create a quality of mind that would provide our students with the necessary sociological skills to critically interrogate different sociological forms, and allow them not simply to understand the subject as an academic discipline but also as a personally transformative experience. It was evident from the feedback from a number of student cohorts that the connection between sociology and the lived experience and personal consciousness had a profound and empowering impact on those who came to develop that quality of mind.